2021
DOI: 10.1007/s11250-021-02887-w
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne zoonotic agents infecting horses from an urban area in Midwestern Brazil: epidemiological and hematological features

Abstract: The emergence of tick-borne diseases has been reported as a serious problem in public health worldwide and many aspects of its epidemiology and effects on the health of its hosts are unclear. We aimed to perform an epidemiological study of tick-borne zoonotic Rickettsia , Borrelia , and Anaplasmataceae in horses from Midwestern Brazil. We also evaluated whether Borrelia spp. and Anaplasmataceae may be associated with hematological disorders i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Campo Grande, in the Midwest region of Brazil, should be monitored since because (i) capybaras that live in urban green areas are highly exposed to Rickettsia of the SFG; (ii) these capybaras presented high tick infestations; (iii) the tick species found parasitizing capybaras have anthropophilic habits; (iv) urban green fragments areas of CG have an intense people flow 2 ; (v) A. dubitatum parasitizing capybaras were found to be infected by Rickettsia of the SFG in the studied areas 5 ; and (vi) Campos et al 6 noticed that 25.6% of 262 sampled horses in the CG were exposed to rickettsia agents of the SFG. Owing to the latent risk of transmission, a surveillance and contingency plan for rickettsioses should be considered for the study area.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Campo Grande, in the Midwest region of Brazil, should be monitored since because (i) capybaras that live in urban green areas are highly exposed to Rickettsia of the SFG; (ii) these capybaras presented high tick infestations; (iii) the tick species found parasitizing capybaras have anthropophilic habits; (iv) urban green fragments areas of CG have an intense people flow 2 ; (v) A. dubitatum parasitizing capybaras were found to be infected by Rickettsia of the SFG in the studied areas 5 ; and (vi) Campos et al 6 noticed that 25.6% of 262 sampled horses in the CG were exposed to rickettsia agents of the SFG. Owing to the latent risk of transmission, a surveillance and contingency plan for rickettsioses should be considered for the study area.…”
mentioning
confidence: 86%
“…Rickettsia , belonging to the spotted fever group (SFG), has been found in CG and its surroundings, showing molecular evidence for R. parkeri in A. sculptum 3 , R. parkeri strain Atlantic rainforest in A. ovale 4 , R. parkeri , R. africae , and R. sibirica in A. dubitatum 5 . Furthermore, Campos et al 6 reported a general seroprevalence of Rickettsia spp. in 25.6% of horses sampled in the CG (n=262); 19.8% were exposed to R. rickettsii , 16.7% to R. parkeri , and 17.5% to R. amblyommatis .…”
mentioning
confidence: 99%
See 1 more Smart Citation